The Disquietude of Duty Assuming Kant - Pacheco, Max Maureira (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
For Kant, the moral duty is determined universally, that is, on account of its form, in the moral norm. However the moral norm is opposed to particularity, determined by what is not the norm itself, hence being the origin of singularity. The singularized norm is opposed, from experience, by its negation in individual cases. To assume Kant demands the reconciliation of the singular, manifested incases, with the universal. This article deals with this question, demonstrating, above all, the practical difficulties linked to the moral experience in its totality.
Keywords: Kant; moral duty; moral experience; moral luck